Monocular visual-inertial odometry system - Cai, Leon Sheng Siang (2018)
A real-time Monocular Visual-Inertial State Estimator (VINS-Mono) is used in this project to replace Global Positional System (GPS) in a confined and indoor environment, where GPS measurements are either unavailable or unacceptably inaccurate, to provide environment information for precise state estimation. This environment information is supported by the monocular Visual-Inertial System (VINS) to carry out Visual-Inertial Odometry (VIO).